High ionic conductivity in fluorite δ-bismuth oxide-based vertically aligned nanocomposite thin films. Issue 7 (3rd February 2022) - Lovett, Adam J.; Wells, Matthew P.; He, Zihao; Lu, Juanjuan; Wang, Haiyan; MacManus-Driscoll, Judith L.
Abstract : First time demonstration of epitaxially stabilised δ-Bi2 O3 phase in vertically aligned nanocomposite thin films, exhibiting very high ionic conductivities of up to 10 −3 S cm −1 at 500 °C. Abstract : δ-Bi2 O3 has long been touted as a potential material for use in solid oxide fuel cells (SOFC) due to its intrinsically high ionic conductivity. However, its limited operational temperature has led to stabilising the phase from >725 °C to room temperature either by doping, albeit with a compromise in conductivity, or by growing the phase confined within superlattice thin films. Superlattice architectures are challenging to implement in functional μSOFC devices owing to their ionic conducting channels being in the plane of the film. Vertically aligned nanocomposites (VANs) have the potential to overcome these limitations, as their nanocolumnar structures are perpendicular to the plane of the film, hence connecting the electrodes at top and bottom. Here, we demonstrate for the first time the growth of epitaxially stabilised δ-Bi2 O3 in VAN films, stabilised independently of substrate strain. The phase is doped with Dy and is formed in a VAN film which incorporates DyMnO3 as a vertically epitaxially stabilising matrix phase. Our VAN films exhibit very high ionic conductivity, reaching 10 −3 S cm −1 at 500 °C. This work opens up the possibility to incorporate thin film δ-Bi2 O3 based VANs into functional μSOFC devices, either as cathodes (by pairing δ-Bi2 O3 with a catalytically active electronic conductor) and/or electrolytes (by incorporating δ-Bi2 O3 with an insulator).